340. Clinical Use of a Multiplex PCR Meningitis/Encephalitis Panel at an Urban Tertiary Care Center. (26th November 2018) - Geadas, Carolina; Asundi, Archana; Lapidot, Rotem; Miller, Nancy; Assoumou, Sabrina A
Abstract: Background: The FilmArray® Meningitis/Encephalitis (ME) Panel (BioFire Diagnostics, Salt Lake City, Utah) is the first multiplex polymerase chain reaction (PCR) test for detection of 14 pathogens in cerebrospinal fluid (CSF) that are commonly associated with meningitis and encephalitis. Its impact on clinical management has not been well evaluated. Our aim was to describe the experience using the ME panel since its implementation at an urban tertiary care center. Methods: We conducted a retrospective chart review of all patients aged >21 who had CSF samples analyzed by the ME panel from January 1 to July 31, 2017. We abstracted demographic, clinical, laboratory, and imaging data to assess ME panel results and their influence on clinical management. Results: We reviewed the charts of 93 patients aged 21 to 85 who had the ME panel performed. Forty-nine (53%) were males and eight (9%) were immunosuppressed. Eight (9%) patients had a positive test for at least one target pathogen: four for a bacterial target ( S. pneumoniae, N. meningitidis, or H. influenza ), three for a viral target (HSV-2 or VZV), and one for both a bacterial and a viral target ( S. pneumoniae and HSV-2). CSF cultures were negative for all five cases with bacteria detected. Confirmatory uniplex PCR was not performed for the positive viral results. Four of the five patients with positive results for a bacterial pathogen had received broad-spectrum antibiotics prior to lumbar puncture. In all five, antibiotics were modified (either started or de-escalated) based on the pathogen identified on the ME panel. All four patients with a positive result for a viral target received anti-viral therapy—in one case this was started empirically, while in the remaining three treatment was started only after the ME panel had resulted. Antibiotic management in the 85 patients with a negative ME panel varied widely based on clinical suspicion and other laboratory data. Three (3%) of the 93 patients had positive cultures for pathogens that are not ME panel targets ( S. aureus and S. hominis ). Conclusion: The ME panel yielded positive results in cases where conventional tests did not, including when antibiotics had been initiated prior to CSF sampling. While a positive ME panel prompted changes in therapy, negative results, in the majority of cases, did not supersede clinical suspicion. Disclosures: N. Miller, BioFire Diagnostics: Paid speaker, single day event (1 time only): 4/6/2017, BioFire Diagnostics, Syndromic Testing Symposium, Burlington, MA, Speaker honorarium.